Mountain Landscapes: The railroad and capture trasandino beauty of The Andes mountains in the poetry of Gabriela Mistral (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The arrival of the Transandean Railway influenced the aesthetic perception that passers-by formed of the local geography. The mountain appears as a fundamental element of poetry in various authors, including Chilean poet Gabriela Mistral. The mountains and its access, from the Elqui to the Andes, are a core element of her poetry, acquiring particular characteristics at each stage of her poetic creation and political vision, which will be analyzed in this article.
Keywords: Gabriela Mistral; Transandean Railway; Mountain; Landscape; Chilean Poetry